Increased Female Athlete Triad Knowledge among Collegiate Dancers following a Brief Educational Video Intervention. Issue 4 (December 2020) - Brown, Katie; Yates, Michelle; Meenan, Melanie; Brown, Ann F.
The female athlete triad (triad) is prevalent among aesthetic athletes, including dancers. However, there is limited research regarding triad knowledge or triad educational interventions among collegiate dancers. This study was intended to help correct that shortage. Participants (N = 24) completed two questionnaires: one assessed demographics, triad risk, and disordered eating (DE) risk; the other measured triad knowledge before and after viewing a 10-minute triad video. Twenty-seven percent of participants were found to be at risk for DE, 27% were at risk for the triad, and 8% were at risk for both. Significant improvements in triad knowledge were observed following the educational video; 4.08 ± 1.83 pre-intervention to 6.75 ± 0.09 post-intervention out of a possible 7, p < 0.001. There were no differences in triad knowledge when comparing freshmen and sophomores to juniors, seniors, and graduate students. This research confirms that triad education should be a continuous component of collegiate dancers' curricula to promote their overall health and wellness, and that the triad video can be an effective educational tool for supporting that goal.